2015
DOI: 10.1002/erv.2344
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affect Mediates the Relationship Between Interpersonal Problems and Binge‐Eating Disorder Symptoms and Psychopathology in a Clinical Sample: A Test of the Interpersonal Model

Abstract: This study evaluated the validity of the interpersonal model of binge-eating disorder (BED) psychopathology in a clinical sample of women with BED. Data from a cross-sectional sample of 255 women with BED were examined for the direct effects of interpersonal problems on BED symptoms and psychopathology, and indirect effects mediated by negative affect. Structural equation modelling analyses demonstrated that higher levels of interpersonal problems were associated with greater negative affect, and greater negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
58
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 39 publications
(72 reference statements)
10
58
1
3
Order By: Relevance
“…The lack of a direct relationship between socializing problems and eating disorder symptoms in the present study was not predicted by the interpersonal models but is consistent with previous clinical and nonclinical research (Ambwani et al, 2015;Ansell et al, 2012;Elliot et al, 2010;Ivanova, Tasca, Hammond, et al, 2015, Ivanova, Tasca, Proulx, et al, 2015Ranzenhofer et al, 2014;Steiger et al, 1999;Tasca et al, 2011). One clinical study (Dakanalis et al, 2015) found a direct association between interpersonal problems and eating disorder symptoms that the relationship between socializing problems and eating disorder symptoms is indirect and reciprocal (Ivanova, Tasca, Proulx, et al, 2015),…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The lack of a direct relationship between socializing problems and eating disorder symptoms in the present study was not predicted by the interpersonal models but is consistent with previous clinical and nonclinical research (Ambwani et al, 2015;Ansell et al, 2012;Elliot et al, 2010;Ivanova, Tasca, Hammond, et al, 2015, Ivanova, Tasca, Proulx, et al, 2015Ranzenhofer et al, 2014;Steiger et al, 1999;Tasca et al, 2011). One clinical study (Dakanalis et al, 2015) found a direct association between interpersonal problems and eating disorder symptoms that the relationship between socializing problems and eating disorder symptoms is indirect and reciprocal (Ivanova, Tasca, Proulx, et al, 2015),…”
Section: Discussionsupporting
confidence: 89%
“…Several community and clinical studies support the validity of the interpersonal model of binge eating for individuals who endorse binge eating or loss of control over eating (Ansell et al, 2012;Elliot et al, 2010;Ivanova, Tasca, Hammond, et al, 2015;Ivanova, Tasca, Proulx, et al, 2015). Several community and clinical studies support the validity of the interpersonal model of binge eating for individuals who endorse binge eating or loss of control over eating (Ansell et al, 2012;Elliot et al, 2010;Ivanova, Tasca, Hammond, et al, 2015;Ivanova, Tasca, Proulx, et al, 2015).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…While the interpersonal model has been widely used to explain binge eating in adults [e.g., 28, 29, 4043], and interpersonal psychotherapy has been adapted as an efficacious treatment for adult binge eating disorder [19, 44], only two studies have simultaneously evaluated all components of the interpersonal model of LOC eating in youth [27, 30]. The first study used structural equation modeling in a large sample of children and adolescents and found that parent-reported social problems were positively associated with children’s reported presence of LOC eating.…”
Section: Introductionmentioning
confidence: 99%
“…First, these studies have utilized vignettes or films to induce negative mood, which may not closely resemble the real-life stressors associated with binge eating. Research suggests that interpersonal stressors are especially powerful triggers for binge eating in the natural environment (Goldschmidt, Wonderlich, et al, 2014; Ivanova et al, 2015). Therefore, a mood induction involving a real-time interpersonal stressor could provide a more ecologically-valid negative affect manipulation.…”
mentioning
confidence: 99%